New Products Development Through Customized Design Based on Customers' Needs. Part 1: Footwear Comfort Parameters. (2016) - Deselnicu, Dana Corina; Vasilescu, Ana Maria; Mihai, Aura; Purcarea, Anca Alexandra; Militaru, Gheorghe
Abstract: The article presents the methodology and results of a fieldwork study conducted in order to obtain new customized footwear products designed based on elderly customers' needs evaluation. Due to the complexity of the results, the outcomes of the study are presented in two articles. This first part outlines the results concerning comfort and design parameters of footwear. The study had an exploratory and descriptive nature, and employed quantitative methodology. The sample consisted in 121 persons from multiple locations in Romania, ranging from 55 to over 75 years of age. The collected data was analyzed on multiple dimensions using a statistic analysis software program. The results generated a methodological approach to emphasize the most important comfort, fit and design constructive characteristics of footwear items that need to be customized, in order to meet the specific needs of elderly people. The paper brings important contributions in customized products design based on customer preferences.